Impacts of Cultivation of Marine Diatoms on the Associated Bacterial Community - Sapp, Melanie (American Society for Microbiology, 2007)
The composition of bacterial communities associated with four diatom species was monitored during isolation and cultivation of algal cells. Strong shifts in the associated communities, linked with an increase in the numbers of phylotypes belonging to members of the Gammaproteobacteria, were observed during cultivation.